Orthodox Church jurisdictions in contemporary Spain = Prawosławne jurysdykcje kościelne we współczesnej Hiszpanii - Dudra, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Orthodoxy in Spain was connected with the influx of the mid-nineteenth century, migrants, main-ly from Greece, Serbia, Bulgaria, Russia and areas of the Middle East. The bases for settling in Spain were both political and economic conditions.
Keywords: Orthodoxy; diaspora; migration; ecclesiastical jurisdictions; prawosławie; migracja; jurysdykcje kościelne